Estimation of ski control - Sakata, T.; Okumura, R.; Kawai, S. (4th International Congress on Science and Skiing, 2007)
INTRODUCTION: One of the authors developed an approach to estimate a skiing with a single ski. By using it, he made clear the effects of various parameters on the skiing. Next, he tried to develop a new approach to simulate the skiing with a pair of skis. As shown in Figure 1(b), during the skiing, various forces and moments act to the skis from the skier. The forces and moments acting to a right ski are not always equal to those acting to a left ski. However, the skiing of the right ski is necessary to be similar with that of the left ski. Figure 2 shows the outline of the new approach attempted to find a solution (Sakata & Yanase, 2006). First, the ski control is assumed. Second, the skiing of the right ski is simulated using the approach for the skiing with a single ski. Third, the skiing of the left ski is simulated in the same way. Fourth, the skiing of the right ski is compared to that of the left ski. Fifth, when they are inadequate as the skiing with a pair of skis, the ski control is modified and the Simulation is carried out again. To simulate the skiing with a pair of skis, as described above, it is necessary to estimate the ski control. In the present study, how to estimate it theoretically will be demonstrated.